Rendre compte des tensions et hégémonies épistémiques qui sous-tendent la production de savoirs sur l’Afrique - Guillaume Beaud (Revue d'anthropologie des connaissances)
Accounting for mechanisms underpinning knowledge production on contemporary Africa tends to oppose two views. On the one hand, the need to encourage the africanisation trend, of both researchers and epistemological frameworks used, in order to grasp the complexity of local empirical dynamics. On the other hand, acknowledging the relevance and historical weight of theoretical apparatuses designed in Western universities, as postcolonial studies. This paper attempts to shed light on such conceptual debate, through an empirical study of the African Identities, an academic journal published in the United Kingdom, advocating to conciliate and promote dialogue between such perspectives. This work relies on the development of a prosopographic and quantitative database compiling both African Identities contributors’ biographical trajectories, academic reference utilised, and countries studied by the published works (2003-2018). In view of epistemological debates that infuse the journal's editorial ambitions and the study of Africa more broadly, the analysis of collected data underlines modalities and limits to the africanisation process of scientific production.